Eryptosis as a New Insight in Malaria Pathogenesis - Scovino, Aline Miranda (2022)
Universidade Federal do Rio de Janeiro. Instituto de Microbiologia Paulo de Góes. Rio de Janeiro, RJ, Brasil / Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Pesquisa em Malária. Rio de Janeiro, RJ, Brasil / Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Imunoparasitologia. Rio de Janeiro, RJ, Brasil.